2013
DOI: 10.1136/jnnp-2013-304920
|View full text |Cite
|
Sign up to set email alerts
|

An early prediction of delirium in the acute phase after stroke

Abstract: A model including age, stroke severity, stroke subtype and infection can be used to identify patients who have a high risk to develop delirium in the early phase of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
1
34
1
Order By: Relevance
“…We did not confirm that older age and greater severity of injury are risk factors (31). How to predict delirium symptoms Domain-specific quality of life (QOL) scores at 28 days, stratified by delirium.…”
Section: Discussionmentioning
confidence: 80%
“…We did not confirm that older age and greater severity of injury are risk factors (31). How to predict delirium symptoms Domain-specific quality of life (QOL) scores at 28 days, stratified by delirium.…”
Section: Discussionmentioning
confidence: 80%
“…Studying the risk factors for neurosurgery delirium, Harasawa and Mizuno () reported postoperative delirium in cerebrovascular surgery patients with high‐risk factors including dehydration, age, underlying disease, and disturbance of consciousness, anxiety or depression. Oldenbeuving, de Kort, van Eck van der Sluijs, Kappelle, and Roks () also suggested that the high‐risk factors for delirium in stroke patients include age, stroke severity, stroke subtype and infection. Naidech, Polnaszek, Berman, and Voss () further suggested that delirium in patients with cerebral haematoma was associated with haematoma sites, such as the right cerebral hemisphere cortical white matter (upper bundle) and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke-related risk factors include greater stroke severity [3], stroke in anterior circulation [3, 10] and specific symptoms of stroke such as aphasia, neglect or hemianopia [4, 8, 11]. The impact of lesion location and stroke type is uncertain [4, 1012]. The predisposing role of environmental factors has not been investigated in stroke, however in non-stroke acute settings, only the use of restrains was significantly associated with higher risk of delirium [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Oldenbeuving et al conducted an analysis on 800 patients with ischemic stroke and described a tool to predict the risk for PSD; the score is based on patients age, stroke severity, stroke subtype and infection [12]. This model has a sensitivity of 76 % and specificity of 81 % for PSD diagnosis.…”
Section: Introductionmentioning
confidence: 99%